2017
DOI: 10.1186/s13054-016-1593-x
|View full text |Cite
|
Sign up to set email alerts
|

Is platelet transfusion associated with hospital-acquired infections in critically ill patients?

Abstract: BackgroundPlatelets are commonly transfused to critically ill patients. Reports suggest an association between platelet transfusion and infection. However, there is no large study to have determined whether platelet transfusion in critically ill patients is associated with hospital-acquired infection.MethodsWe conducted a multi-centre study using prospectively maintained databases of two large academic intensive care units (ICUs) in Australia. Characteristics of patients who received platelets in ICUs between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
39
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 19 publications
3
39
0
3
Order By: Relevance
“…Similar to our findings, studies by Karkouti and colleagues and Sreeram and coworkers assessing patients receiving nonleukoreduced and leukoreduced cellular blood products, respectively, reported no association between transfusion and infection . In contrast, a recent study assessing platelet transfusion in critically ill intensive care unit (ICU) patients demonstrated that after adjustment for patient severity and other blood component use, platelet transfusion in this patient population was independently associated with ICU‐acquired infection …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar to our findings, studies by Karkouti and colleagues and Sreeram and coworkers assessing patients receiving nonleukoreduced and leukoreduced cellular blood products, respectively, reported no association between transfusion and infection . In contrast, a recent study assessing platelet transfusion in critically ill intensive care unit (ICU) patients demonstrated that after adjustment for patient severity and other blood component use, platelet transfusion in this patient population was independently associated with ICU‐acquired infection …”
Section: Discussionsupporting
confidence: 89%
“…16,18 In contrast, a recent study assessing platelet transfusion in critically ill intensive care unit (ICU) patients demonstrated that after adjustment for patient severity and other blood component use, platelet transfusion in this patient population was independently associated with ICU-acquired infection. 20 WBC-mediated transfusion-related immunomodulation is a transient immunosuppression that may occur following transfusion of allogeneic blood. 21 While the exact mechanisms, and many are proposed, are not yet established, it is hypothesized that WBC release of cytokines modulates the balance between a Type 1 and Type 2 immune response, leading to increased rates in postoperative bacterial infections, organ dysfunction, and length of stay.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason is that most patients who are transfused with PC are immunocompromised and thus vulnerable to bacterial infection. 1,2 Significant numbers of septic reactions and fatal outcomes related to PC transfusion have been reported from many countries. [3][4][5][6] Various interventions to mitigate these consequences of PC transfusion have been proposed, as follows.…”
Section: Discussionmentioning
confidence: 99%
“…The major reason for this compared with red cell or plasma components is a high bacterial load derived from storing PC at 20‐24°C, which enables vigorous bacterial proliferation in PC during the preservation process. Another reason is that most patients who are transfused with PC are immunocompromised and thus vulnerable to bacterial infection . Significant numbers of septic reactions and fatal outcomes related to PC transfusion have been reported from many countries …”
mentioning
confidence: 99%
“…Marly Voquer et al [15] ascribed the stronger clot in the FIBTEM assay of rotational thromboelastometry at a stronger contribution of platelets in feline blood of people than cats. Aubron et al [16] independently associated platelet transfusion with 5.5-fold more hospital-acquired infections in the ICU (p < 0.01), with 2.56%-fold more infections (p < 0.001). Navas Carrillo et al [17] described the formation of luminal thrombi secondary to platelet activation and the release of thrombogenic elements within the atherosclerotic lesions in acute coronary syndromes.…”
Section: Discussionmentioning
confidence: 99%